Nonsense-mediated mRNA decay and development: shoot the messenger to survive?. (24th November 2010) - Vicente-Crespo, Marta; Palacios, Isabel M.
Abstract : NMD (nonsense-mediated mRNA decay) is a surveillance mechanism that degrades transcripts containing nonsense mutations, preventing the translation of potentially harmful truncated proteins. Although the mechanistic details of NMD are gradually being understood, the physiological role of this RNA surveillance pathway still remains largely unknown. The core NMD genes Upf1 (up-frameshift suppressor 1) and Upf2 are essential for animal viability in the fruitfly, mouse and zebrafish. These findings may reflect an important role for NMD during animal development. Alternatively, the lethal phenotypes of upf1 and upf2 mutants might be due to their function in NMD-independent processes. In the present paper, we describe the phenotypes observed when the NMD factors are mutated in various organisms, and discuss findings that might shed light on the function of NMD in cellular growth and development of an organism.